Strontium zirconate heterogeneous catalyst for biodiesel production: Synthesis, characterization and catalytic activity evaluation - de Oliveira Lima, Jose Renato [UNESP]; Ghani, Yussra Abdul [UNESP]; da Silva, Rondenelly B.; Batista, Francisco Marcos C.; Bini, Rafael Admar; Varanda, Laudemir Carlos; Oliveira, Jose Eduardo de [UNESP] (Elsevier B.V., 2012)
Strontium zirconate oxide was synthesized by co-precipitation and the citrate route and was evaluated as a heterogeneous catalyst for biodiesel production. The catalyst samples were characterized by XRD, FTIR, and TG, and catalytic activity was measured based on the ester content of the biodiesel produced that was quantified by GC. The co-precipitate samples were obtained in alkaline pH and had a mixture of the perovskite and pure strontium and zirconium oxide phases. Ester conversion using these samples was approximately 1.6%, indicating no catalytic activity. The citrate route was more efficient in producing perovskite when carried out at pH 7-8; excess SrCO3 was found on the catalyst surface due to CO2 adsorption, thus demonstrating no catalytic activity. The same synthesis carried out at pH 2 resulted in free OH- groups, with a small amount of the carbonate species that produced ester yield values of 98%. Therefore, matrices based on strontium zirconate produced via the citrate route in acidic media are potential heterogeneous catalysts for transesterification. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Strontium zirconate; Citrate route; Heterogeneous catalyst; Biodiesel